ANALISIS OVERREACTION HYPOTHESIS PADA HARGA SAHAM - Eka Radiyanti; Sri Hasnawati (Faculty of Economics and Business University of Lampung, 2024)
The purpose of this research is to see if there is an overreaction hypothesis on stock prices on the Indonesia Stock Exchange. This study's population consists of 229 manufacturing companies registered on the Indonesia Stock Exchange between 2018 and 2022. This study's sample was drawn using a purposive sampling approach, yielding a sample of 127 companies. The study used a significance t test which was processed using SPSS 22 software. The research period is an annual period. Shares are classified into 2 types, namely winner stocks and loser stocks. The results of the study show that winner and loser stocks have experienced several reversals, but these symptoms cannot be proven statistically. As a result, there is no overreaction hypothesis for manufacturing companies registered on the Indonesia Stock Exchange between 2018 and 2022. Keywords: Overreaction Hypothesis, Winner Stocks, Loser Stocks, Abnormal Return Abstrak Tujuan dari penelitian ini adalah untuk melihat apakah terdapat overreaction hypothesis terhadap harga saham di Bursa Efek Indonesia. Populasi penelitian ini terdiri dari 229 perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2018-2022. Pengambilan sampel penelitian ini menggunakan pendekatan purposive sampling, sehingga menghasilkan sampel sebanyak 127 perusahaan. Penelitian menggunakan uji signifikansi t yang diolah dengan menggunakan software SPSS 22. Periode penelitian adalah periode tahunan. Saham diklasifikasikan menjadi 2 jenis, yaitu saham winner dan saham loser. Hasil penelitian menunjukkan bahwa saham winner dan loser telah mengalami beberapa kali pembalikan, namun gejala tersebut tidak dapat dibuktikan secara statistik. Hasilnya, tidak ada overreaction hypothesis untuk perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2018-2022. Kata Kunci: Overreaction Hypothesis, Winner Stocks, Loser Stocks, Abnormal Return